Resuscitative endovascular balloon occlusion of the aorta for uncontrolled haemorrahgic shock as an adjunct to haemostatic procedures in the acute care setting. Issue 1 (December 2016) - Tsurukiri, Junya; Akamine, Itsurou; Sato, Takao; Sakurai, Masatsugu; Okumura, Eitaro; Moriya, Mariko; Yamanaka, Hiroshi; Ohta, Shoichi
Abstract Background Haemorrhagic shock is a major cause of death in the acute care setting. Since 2009, our emergency department has used intra-aortic balloon occlusion (IABO) catheters for resuscitative endovascular balloon occlusion of the aorta (REBOA). Methods REBOA procedures were performed by one or two trained acute care physicians in the emergency room (ER) and intensive care unit (ICU). IABO catheters were positioned using ultrasonography. Collected data included clinical characteristics, haemorrhagic severity, blood cultures, metabolic values, blood transfusions, REBOA-related complications and mortality. Results Subjects comprised 25 patients (trauma, n = 16; non-trauma, n = 9) with a median age of 69 years and a median shock index of 1.4. REBOA was achieved in 22 patients, but failed in three elderly trauma patients. Systolic blood pressure significantly increased after REBOA (107 vs. 71 mmHg, p < 0.01). Five trauma patients (20 %) died in ER, and mortality rates within 24 h and 60 days were 20 % and 12 %, respectively. No REBOA-related complications were encountered. The total occlusion time of REBOA was significantly lesser in survivors than that in non-survivors (52 vs. 97 min, p < 0.01). Significantly positive correlations were found between total occlusion time of REBOA and shock index (Spearman'sr = 0.6) and lactate concentration (Spearman'sr = 0.7) in survivors. Conclusion REBOA can be performed in ER and ICU with a high degree of technical success. Furthermore, correlations between occlusion time and initial high lactate levels and shock index may be important because prolonged occlusion is associated with a poorer outcome.